Nicolau syndrome caused by the "self-injection" of diclofenac - Selcuk Yaylaci; Hasan Tahsin Gozdas; Osman Ayyildiz; Sibel Kandemir Tugcugil; Mustafa Volkan Demir; Ahmet Bilal Genc; Ceyhun Varim; Onder Tosun; Gokhan Demiral (Wolters Kluwer Medknow Publications, 2016)
Nicolau syndrome (NS) is a rare injection-related local complication. Some drugs have been implicated to cause this syndrome. Several cases were previously reported in the literature. In this paper, an interesting case of NS in a 30-year-old male patient after intramuscular self-injection of diclofenac was presented.